The horizontal and vertical spatial orientation and its role in the metaphorical approach to inflation in German economic press - Gierzyńska, Marta Anna (Papers in Linguistics, 2024)
Economy and its problems have been a matter of public interest for a long time now. This attitude can also be applied to the issue of inflation because of its influence on the functioning of economy, which is systematically discussed in current media reports in many countries. To understand the essence and the development of inflation, an analysis of articles found in German economic press was conducted. The analysis is based on the concept of image schema by Mark Johnson (1987). The identified conceptual metaphors are based on the schemata of the road and the scale, which points to the horizontal and vertical conceptualization of this phenomenon. This, in turn, proves that basic and direct human experience finds its reflection also in the reception and understanding of the specialised content. The presented theoretical considerations emphasize the changing approach to the presence and role of metaphor in professional and scientific discourse and refer to the description of the most important assumptions of the Cognitive Theory of Metaphor proposed by Lakoff and Johnson (1980), which are relevant for the empirical part of the article.